2015
DOI: 10.1179/2042618615y.0000000014
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of trigger point dry needling for multiple body regions: a systematic review

Abstract: The majority of high-quality studies included in this review show measured benefit from TDN for MTrPs in multiple body areas, suggesting broad applicability of TDN treatment for multiple muscle groups. Further high-quality research is warranted to standardise TDN methods to determine clinical applicability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 36 publications
1
64
0
1
Order By: Relevance
“…This improves the generalizability of our findings to physical therapists, and provides evidence that dry needling may be an effective treatment technique when used by physical therapists trained in its use in an appropriate patient for the management of musculoskeletal pain. The findings of this review are in agreement with those of previous reviews, 4,5,11,20,23,30 in that dry needling may be superior to no treatment or sham needling in reducing pain in the immediate to 12-week follow-up period. Results from this review differ from those of previous reviews 20,23,40 showing an overall treatment effect of dry needling compared to standard care/other treatment; the present review found that dry needling performed by physical therapists provided a small treatment effect compared to other interventions performed by physical therapists for reducing pain and increasing PPT.…”
Section: Discussion Tsupporting
confidence: 80%
See 3 more Smart Citations
“…This improves the generalizability of our findings to physical therapists, and provides evidence that dry needling may be an effective treatment technique when used by physical therapists trained in its use in an appropriate patient for the management of musculoskeletal pain. The findings of this review are in agreement with those of previous reviews, 4,5,11,20,23,30 in that dry needling may be superior to no treatment or sham needling in reducing pain in the immediate to 12-week follow-up period. Results from this review differ from those of previous reviews 20,23,40 showing an overall treatment effect of dry needling compared to standard care/other treatment; the present review found that dry needling performed by physical therapists provided a small treatment effect compared to other interventions performed by physical therapists for reducing pain and increasing PPT.…”
Section: Discussion Tsupporting
confidence: 80%
“…Results from this review differ from those of previous reviews 20,23,40 showing an overall treatment effect of dry needling compared to standard care/other treatment; the present review found that dry needling performed by physical therapists provided a small treatment effect compared to other interventions performed by physical therapists for reducing pain and increasing PPT. It is possible that differences between dry needling and other physical therapy interventions were found in the current review because previous reviews 4,5,20,23,31 commonly have compared dry needling to other types of needling (eg, wet needling, which is not performed by physical therapists). In the current review, dry needling was compared to (1) exercise/soft tissue mobilization/joint mobilization for postsurgical shoulder pain, 2 (2) proprioception/strengthening for ankle pain, 35 (3) ischemic compression techniques in 4 studies on neck pain, 6,24,36,43 (4) orthopaedic manual therapy consisting of joint mobilization of the cervical and thoracic spine for neck pain, 6 (5) active stretching for neck pain, 12 and (6) percutaneous electrical nerve stimulation for chronic lower back pain.…”
Section: Discussion Tmentioning
confidence: 80%
See 2 more Smart Citations
“…We suggest that the authors amend their strongly worded conclusions to more closely match what the actual trial data suggest that despite strong anecdotal support 28 and positive reviews (that are flawed), 1,29,30 the positive influence of dry needling is overstated in this systematic review. 31 …”
mentioning
confidence: 99%